Kebutuhan Seksual Menjadi Penyebab Utama Tingginya Angka Perceraian - Umar Faruq (Lembaga Pengembangan Kinerja Dosen, 2023)
In Islam, marriage is a sunnatullah that applies to every creature. Marriage cannot always achieve its essential goals, one of which can be seen in divorce. It can even be stated that the most sad event in marriage is divorce, so God really hates it. So the author raised the theme